PERILAKU MAKAN BURUNG MERBAH CERUCUK (Pycnonotus goiavier) DI KAWASAN HUTAN TAHURA POCUT MEURAH INTAN - Safrika, Dessy; Wati, Cut Linda; Ritong, Rizky Aleyda; Nafisah, Ulfa; Ahadi, Rizky; Rahmanda, Syahrul (Prosiding Seminar Nasional Biologi, Teknologi dan Kependidikan, 2024)
The Merbah Cerucuk bird species (Pycnonotus goiavier) with the order Passeriformes, Family Pycnonotidae and Genus Pycnonotus is an important part of the forest ecosystem, this bird plays a role in dispersal of seeds, controlling insects, and maintaining ecosystem balance. The aim of this research is to observe the feeding behavior of Merbah Cerucuk birds in the Pocut Meurah Intan Grand Forest Park area with the method used being focal animal sampling and qualitative descriptive data analysis. Merbah cerucuk birds eat by pulling small fruit directly from the stalk with their beak. The cerucuk merbah bird will swallow small fruit directly, some merbah birds are seen eating fruit by peeling the fruit or ripping and tearing the fruit using their beaks until they are small and then swallowed.Keywords: Pocut Meurah Intan Grand Forest Park, Merbah Cerucuk Bird (Pycnonotus goiavier), Feeding behavior.